2000
DOI: 10.5860/crl.61.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Presentation Formats for Instruction: Teaching First-Year Students

Abstract: First-year experience (FYE) programs offer librarians opportunities to teach new students in a comprehensive fashion. However, large FYE programs can place demands on user education programs that are dif ficult to meet. Instruction librarians at the University at Albany sought to address this dilemma by developing a Web-based instructional module for one class session. The module was used by a segment of students in the Project Renaissance FYE program, whereas another segment re ceived instruction by a librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 4 publications
(1 reference statement)
1
29
1
1
Order By: Relevance
“…One concern of librarians and teaching faculty alike is the fact that CAI tends to reduce personal contact time between student and librarian. 13 Students may also lose the chance to connect with "the physical and social space of the library. "…”
mentioning
confidence: 99%
“…One concern of librarians and teaching faculty alike is the fact that CAI tends to reduce personal contact time between student and librarian. 13 Students may also lose the chance to connect with "the physical and social space of the library. "…”
mentioning
confidence: 99%
“…The authors concluded that CAI, although timeconsuming and expensive, was a worthwhile endeavor and likely alternative to conducting face-to-face library instruction. This research was supported a few years later by Germain, Jacobson, and Kaczor (2000) who found that their web-based instructional model improved students' library skills as effectively as in-person library instruction. While academic librarians continued to embrace online methods of instruction, Australian librarians at Deakin University published an article comparing faceto-face with standalone and meditated tutorials (Churkovich & Oughtred, 2002).…”
Section: Literature Reviewmentioning
confidence: 67%
“…The probability was greater than .05 that the observed difference between means in the total score would have occurred by chance if the null hypothesis were true. Although it is not uncommon for controlled studies to yield insignificant results after comparing instructional approaches (Germain et al, 2000;Hess, 2014;Kaplowitz & Contini, 1998;Yong, Levy, & Lape, 2015), such outcomes should always be considered alongside effect sizes (e.g., Walton & Hepworth, 2012), as well as within the larger research framework. In this current study, the results can be evaluated within the specific context of a quasi-experimental design: namely, did the approach itself limit the impact of the video series on students' research self-efficacy?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations